Plastic In Skincare Cosmetics: An Investigation of the Acceptance of Plastic Packaging and Micro-Plastics When Buying Skincare Products (International Journal of Applied Research in Management and Economics, 2020)
Never before has so much plastic existed within the environment as is currently the case. Cosmetics are a significant part of the plastic problem, both in terms of microplastics in the ingredients and through plastic-containing packaging. Generation Y is often seen as being environmentally conscious and sustainable. Contrary to this, however, Generation Y has proven to be carefree when buying plastic cosmetics. This article is intended to clarify the question of why German women of Generation Y buy plastic-contaminated, caring facial cosmetics, even though they are aware of possible damage. Results of an online survey (N=337) and a qualitative survey with experts revealed that the leading causes for the purchase of plastic-containing, caring cosmetics include the lack of plastic-free alternative products, the lack of transparency of product declarations and the enormous amount of time involved in the search for plastic-free cosmetic.